Student, teacher and parent perspectives on senior cycle education - Emer Smyth; Selina MacCoy; Joanne Banks (The Economic and Social Research Institute (ESRI), 2019)
Research conducted by the ESRI shows a strong appetite among students, parents and teachers for changing senior cycle education, which incorporates Transition Year, 5th Year and 6th Year. A study presenting their viewpoints shows that they mainly focus on changing the approach to assessment, with the objectives of reducing stress and capturing a broader range of student skills. The report analyses findings from two rounds of consultation with 41 schools conducted by the National Council for Curriculum and Assessment (NCCA) as part of a broader review of senior cycle. The study was carried out in the school year 2018-19 and recorded what participants believe are the positive and negative aspects of the current senior cycle programme and how they believe current challenges could be addressed.
Keywords: 330